Charakterystyka warunków żeglugowych Brdy skanalizowanej = Characteristics of shipping conditions of canalized part of the Brda River - Daniel Józefowicz; Dawid Aleksander Szatten; Hubert Rabant (Kazimierz Wielki University, 2016)
Józefowicz Daniel, Szatten Dawid, Rabant Hubert. Charakterystyka warunków żeglugowych Brdy skanalizowanej = Characteristics of shipping conditions of canalized part of the Brda River. Journal of Education, Health and Sport. 2016;6(12):564-574. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.216406 http://ojs.ukw.edu.pl/index.php/johs/article/view/4100         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 20.12.2016.       Charakterystyka warunków żeglugowych Brdy skanalizowanej Characteristics of shipping conditions of canalized part of the Brda River   Daniel Józefowicz, Dawid Szatten, Hubert Rabant   Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Instytut Geografii, ul. Mińska 15, 85-428 Bydgoszcz   STRESZCZENIE             Ujściowy odcinek Brdy stanowi kluczowy fragment Międzynarodowej Drogi Wodnej E-70. Łączy on rzekę Wisłę z Kanałem Bydgoskim, stanowiącym przedłużenie szlaku wodnego w kierunku dorzecza Odry. W artykule scharakteryzowano stan infrastruktury wodnej pod kątem istniejących przeszkód nawigacyjnych, warunków głębokościowych oraz zagospodarowania turystycznego. Odniesiono się ponadto do obowiązujących przepisów krajowych dla śródlądowych dróg wodnych. Umożliwiło to ocenę bezpieczeństwa analizowanej części rzeki Brdy do prowadzenia żeglugi.   ABSTRACT             The mouth of the Brda River is a key part of the International Waterway E-70. It connect the Vistula River with the Bydgoszcz Canal, which is an extension of the waterway in the direction of the Odra River Basin. The research characterized the state of the water infrastructure in terms of existing barriers of navigation, depth conditions and tourist development. Furthermore makes reference to the applicable national regulations for inland waterways. This allowed to prepare safety assessment of the analysed part of the Brda River for inland shipping.   SŁOWA KLUCZOWE: Brda, żegluga śródlądowa, Międzynarodowa Droga Wodna E-70 KEY WORDS: Brda River, inland shipping, International Waterway E-70